2019
DOI: 10.1111/ans.15611
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age, comorbidities and complications in head and neck cancer patients undergoing curative surgery

Abstract: Background: Both age and comorbidity are accepted as significant prognostic factors for adverse perioperative outcomes in major surgery. Elderly patients may be overlooked for radical treatment for fear of poor perioperative outcome. We aim to assess the relationship between age, comorbidities and post-operative outcomes in a tertiary head and neck unit. Methods: A retrospective analysis was undertaken on 651 patients who underwent surgery for head and neck cancer at a tertiary hospital between 2007 and 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…13,14 Our findings suggest that these factors can increase intraoperative technical difficulties and prolong operative times, thus resulting in a higher rate of intraoperative complications, such as bleeding, tracheostomy tube displacement, and respiratory arrest. Previous studies have reported that increasing comorbidity resulted in higher rates of postoperative infection, cardiac events, respiratory failure, and mortality in the late postoperative stage, 15,16 which was also established in our study. According to univariable analysis, the number of comorbidities was a significant risk factor for late postoperative complications and the occurrence of all complications, with pneumonia being the most frequent.…”
Section: Discussionsupporting
confidence: 88%
“…13,14 Our findings suggest that these factors can increase intraoperative technical difficulties and prolong operative times, thus resulting in a higher rate of intraoperative complications, such as bleeding, tracheostomy tube displacement, and respiratory arrest. Previous studies have reported that increasing comorbidity resulted in higher rates of postoperative infection, cardiac events, respiratory failure, and mortality in the late postoperative stage, 15,16 which was also established in our study. According to univariable analysis, the number of comorbidities was a significant risk factor for late postoperative complications and the occurrence of all complications, with pneumonia being the most frequent.…”
Section: Discussionsupporting
confidence: 88%
“… 2 , 24 , 36 , 51 Male patients are more likely to experience postoperative complications that are associated with PORT delay and demonstrate worse overall survival compared to female patients. 52 Although there is not enough evidence to declare a relationship between gender/sex and delayed PORT, Mazul et al found that although female patients with HNSCC had greater overall survival than males, Black female patients had significantly worse survival rates than White and Hispanic male patients. 53 This interaction would be interesting to study in rates of delayed PORT.…”
Section: Resultsmentioning
confidence: 99%
“…Besides comorbidities, we know that age can affect surgical decision making in older adults. In a study of head and neck cancers, Stepherd et al (14) found that age alone had no effect on postoperative mortality, complications, and length of hospital stay. Cost is also considered in deciding on surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the evaluation of hemogram parameters, this study examined the older adults according to whether they were approved for surgery or considered inoperable. In the literature, mortality analyses were mostly performed in studies on gastric or tumor surgery, and surgical decision differs according to the stages of the disease or diagnosis (14,15). However, acute abdominal pathologies may not always require surgery.…”
Section: Discussionmentioning
confidence: 99%